(untitled) (Research, Society and Development, 2021)
This paper analyzes the Brazilian Military Regime (1964-1984) in terms of the institutionalization of repression and the military’s geopolitical project and the break with democracy. Guided by the National Security Doctrine, the Armed Forces are called to think strategies that allow the security of the country, according to its premises. To justify this geopolitical conception, we analyze the context of 1964 Military Coup in Brazil and the way the National Security Doctrine verified the presence of an internal threat to the Brazilian State and civil society, that is, encouraging the constitution of a dictatorial state to protect the national territory. The research methodology adopted was a literature review with analysis of documents and data from the Truth Commission. Among the results obtained, we highlight that the 1964 Military Coup in Brazil and the construction of the Military Regime originated from the geopolitical discourse of the Brazilian military. Moreover, to save national security, the disturbance of Brazilian democracy and the taking of authoritarian actions in the search for the “internal and subversive enemy” was justified.